Effect of Agricultural Land Function Transfer on Urban Development in North Kuta District - S, I Gusti Ngurah Ady Putra; Suartika, Gusti Ayu Made; Dwijendra, Ngakan Ketut Acwin (Universitas Ibn Khaldun Bogor, 2024)
Land use change in general concerns the transformation in allocating land resources from one designation to another. The aims of this study were (1) to identify problems with the conversion of agricultural land, especially paddy fields (2) to analyze its spatial pattern and the influencing factors, and (3) to analyze policies related to the conversion of agricultural land. This study used a qualitative approach, collecting data using interviews, observation, and documentation techniques. The data analysis technique used is descriptive qualitative. The research was conducted in North Kuta District, Badung Regency. The conclusions from this study are (1) the conversion of agricultural land to non-agricultural use is strongly influenced by the dynamics of very rapid urban growth, both from a demographic, economic, and physical perspective. 2) The spatial pattern of the conversion of paddy fields is influenced by socio-economic factors, including urban population growth, growth and shifts in economic structure, growth of land-using agricultural households, and changes in the area of land tenure. 3) The policy related to controlling the conversion of agricultural land is the consistency of the implementation of the District RDTR as the key to preventing the conversion of agricultural land to non-agricultural land.